Damage tolerance in additively manufactured ceramic architected materials. Issue 13 (October 2022) - Thiraux, Raphael; Dupuy, Alexander D.; Lei, Tianjiao; Rupert, Timothy J.; Mohraz, Ali; Valdevit, Lorenzo
Abstract: Technical ceramics exhibit exceptional high-temperature properties, but unfortunately their extreme crack sensitivity and high melting point make it challenging to manufacture geometrically complex structures with sufficient strength and toughness. Emerging additive manufacturing technologies enable the fabrication of large-scale complex-shape artifacts with architected internal topology; when such topology can be arranged at the microscale, the defect population can be controlled, thus improving the strength of the material. Here, ceramic micro-architected materials are fabricated using direct ink writing (DIW) of an alumina nanoparticle-loaded ink, followed by sintering. After characterizing the rheology of the ink and extracting optimal processing parameters, the microstructure of the sintered structures is investigated to assess composition, density, grain size and defect population. Mechanical experiments reveal that woodpile architected materials with relative densities of 0.38–0.73 exhibit higher strength and damage tolerance than fully dense ceramics printed under identical conditions, an intriguing feature that can be attributed to topological toughening.